Efficacy of Dexmedetomidine as an Adjuvant in Subarachnoid Block versus Transversus Abdominis Plane Block in Patients Undergoing Total Abdominal Hysterectomy under Spinal Anaesthesia: A Double-blinded Randomised Clinical Study - Rachana S Kori; J Vasantha Kumar; Shilpa Nijalingappa Bingi; Sharmila Somayaji (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Postoperative pain continues to be a major concern in patients undergoing abdominal surgeries despite advances in regional anaesthesia. Dexmedetomidine is found to have analgesic properties, hence used as an adjuvant for enhancing postoperative analgesia in both central neuraxial and peripheral nerve block. Aim: To compare the efficacy of dexmedetomidine as an adjuvant in subarachnoid block versus Transversus Abdominis Plane (TAP) block in patients posted for total abdominal hysterectomy under spinal anaesthesia. Materials and Methods: This double-blinded randomised clinical study was conducted at Bangalore Medical College and Research Institute, Bengaluru, Karnataka, India. A total of 70 patients undergoing elective total abdominal hysterectomy under subarachnoid and TAP block. Patients were randomly allocated into two groups (n=35 each). Patients were administered intrathecal 2.8 mL of 0.5% hyperbaric bupivacaine. At the end of surgery, an ultrasound-guided bilateral TAP block was administered using 20 mL of 0.25% bupivacaine on each side (total volume made up to 22 mL). Group SD (Spinal Dexmedetomidine group) received 5 µg (0.05 mL) of dexmedetomidine intrathecally and Group TD (TAP Dexmedetomidine group) received 25 µg dexmedetomidine in TAP block. Haemodynamic parameters, postoperative Visual Analogue Scale (VAS) pain score, time to first rescue analgesia, total rescue analgesic consumption in 24 hours, and sedation scores were noted. Data were analysed using an independent samples t-test and a Chi-square test. A p-value of